Limites procedimentais da positivação e realização da segurança jurídica - Dacal, Leoncio Ogando (2013)
Adopting the theoretical and methodological assumptions of logical semantics constructivism, this paper aims to highlight the strict bond established between the role played by the legal system, its operational closure and the process of, using the general and abstract legislation, applying it to an specific case. This evidence allowed the formulation a conception of legal certainty that seeks to restrict the possibilities of interpretation by requiring a purification process of dialecticalargumentative nature that allows dissent, but also seeks for an intersubjective agreement. Furthermore, it requires that the sense is grounded on the system as a condition of prevalence, besides being subjected to a temporal cut, as inserted in a system designed to produce decisions